2017
DOI: 10.1111/ene.13464
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria for adult‐onset leukoencephalopathy with axonal spheroids and pigmented glia due to CSF1R mutation

Abstract: Background and purpose To establish and validate diagnostic criteria for adult‐onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) due to colony‐stimulating factor 1 receptor (CSF1R) mutation. Methods We developed diagnostic criteria for ALSP based on a recent analysis of the clinical characteristics of ALSP. These criteria provide ‘probable’ and ‘possible’ designations for patients who do not have a genetic diagnosis. To verify its sensitivity and specificity, we retrospectively applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 15 publications
3
80
1
Order By: Relevance
“…Considering that genome‐wide association studies have not identified any associations near CSF1R gene in ischemic stroke cohorts and any disease associations of p.Glu573Lys variant have not been reported in the Cerebrovascular Disease Knowledge Portal , it is unlikely that the p.Glu573Lys variant is directly associated with the patient's stroke. The patient did not have typical clinical findings of ALSP and did not fulfill the diagnostic criteria for ALSP , but white matter abnormalities unrelated to the recent infarct were evident. However, the patient had vascular risks.…”
Section: Discussionmentioning
confidence: 95%
“…Considering that genome‐wide association studies have not identified any associations near CSF1R gene in ischemic stroke cohorts and any disease associations of p.Glu573Lys variant have not been reported in the Cerebrovascular Disease Knowledge Portal , it is unlikely that the p.Glu573Lys variant is directly associated with the patient's stroke. The patient did not have typical clinical findings of ALSP and did not fulfill the diagnostic criteria for ALSP , but white matter abnormalities unrelated to the recent infarct were evident. However, the patient had vascular risks.…”
Section: Discussionmentioning
confidence: 95%
“…). Computed tomography of the head did not demonstrate calcifications, which are helpful in diagnosing ALSP . According to Konno et al , however, calcifications may often be overlooked because they are extremely small, which could have been the case with this patient.…”
Section: Case Presentationmentioning
confidence: 68%
“…Computed tomography of the head did not demonstrate calcifications, which are helpful in diagnosing ALSP. 1 According to Konno et al, 1 however, calcifications may often be overlooked because they are extremely small, which could have been the case with this patient. Single-photon emission computed tomography with technetium-99m ethyl cysteinate dimer revealed relative hypoperfusion mainly in the bilateral frontal lobe areas, including the left Broca's area.…”
Section: Case Presentationmentioning
confidence: 77%
See 2 more Smart Citations